Fractures of the forearm and carpus. Issue 3 (March 2016) - Armstrong, Dan
Abstract: Fractures of the carpus and forearm include a wide range of injuries, but all have their own complexities and nuances. Injuries that are unrecognized, or inappropriately managed can lead to significant pain and disability later on. This article looks at common and less common injuries and the considerations required for each.